Impaired emotional categorisation in young people at increased familial risk of depression. - Mannie, Z; Bristow, G; Harmer, C; Cowen, P (2007)
Negative biases in emotional information processing are characteristic of patients with acute depression and may persist after clinical recovery. It is not clear, however, whether such biases are present before the onset of the depressive disorder. The aim of the present study was to examine whether young people at risk of depression, by virtue of having a depressed biological parent (FH+), demonstrate negative biases in tasks of emotional facial recognition and emotional categorization. We also assessed whether task performance and the influence of parental depression are modified by allelic variation in the serotonin transporter (5HTT) gene. We found that the FH+ participants did not show evidence of negative biases relative to matched controls. They were, however, significantly slower to perform a task of emotional categorization. 5HTT genotype did not influence emotional processing significantly. We conclude that negative biases in emotional processing do not appear to be present in people with a family history of depression. However, impairment in emotional categorization could identify a high-risk phenotype and may indicate that people at genetic risk of depression have difficulty in using "mood as information".